(untitled) (Pedagogy of Higher and Secondary Education, 2009)
In article modeling as a method of scientific-an knowledge is analyzed. It is proved, that the methodology of development and a substantiation of pvlyan technologies и a principle of synthesis philosophical, sc ientific-general concepts and their projection in professional, polyart preparation of the future teacher of music; the contents and structure of the semantic model caused by features recognition on the basis of interaction arts is specified; the structure of an art-pedagogical situation in a context of application polyart technologies is concretized, parameters of the polyart-colloquial approach in conditions of modelling art allocated by the example texts of culture, motion picture arts.